Development of the NPL gamma-ray spectrometer NANA for traceable nuclear decay and structure studies. (March 2016) - Lorusso, G.; Shearman, R.; Regan, P.H.; Judge, S.M.; Bell, S.; Collins, S.M.; Larijani, C.; Ivanov, P.; Jerome, S.M.; Keightley, J.D.; Lalkovski, S.; Pearce, A.K.; et al.
Abstract: We present a brief report on the progress towards the construction of the National Nuclear Array (NANA), a gamma-ray coincidence spectrometer for discrete-line nuclear structure and decay measurements. The proposed spectrometer will combine a gamma-ray energy resolution of approximately 3% at 1 MeV with sub-nanosecond timing discrimination between successive gamma rays in mutually coincident decay cascades. We also review a number of recent measurements using coincidence fast-timing gamma-ray spectroscopy for nuclear structure studies, which have helped to inform the design criteria for the NANA spectrometer. Highlights: Design of gamma-ray spectrometer for radioactivity standardizations is presented. Commissioning of digitized, 1 GHz data acquisition system for NANA array. Overview of LaBr3 spectroscopy in nuclear decay studies worldwide given. Effect of 138 La internal radioactivity as a source of background are discussed.